Friction coefficient estimation in shaft/bush interference using finite element model updating. (November 2015) - Seifi, Rahman; Abbasi, Kaveh
Abstract: Reliable finite element modeling has a great degree of importance for studies related to the mechanical design in industry. Finite element modeling is often associated with some uncertainties. Model updating is a tool which can be used to overcoming these uncertainties. This method uses experimental data of the structural components to modify the initial FE model. A typical use of model updating is for interference joint of a shaft and bush. In the modeling of the interference joint for known materials, an approximate value is assumed for friction coefficient of contact areas. Based on intuition, engineering judgments or previous tests, it is difficult to accurately estimate this coefficient. In this paper, model updating is used to estimate and update the friction coefficient in the contact surface of interference shaft and bush joints. Suitable experiments were conducted and the initial finite element model was modified based on the experimental extraction strength of interference fit joints. Finally, typical values of stress fields were extracted from the new model with an updated value of the friction coefficient. Highlights: Model updating can be used for modification of the FE model of interference joints. Friction coefficient can be estimated precisely by model updating of the interference. Roughness of surfaces must be imported to model for exact determination of friction coefficient.